The political economy of development - Faaland, Just (Bloomsbury academic collections. Economics., 2013)
"Economic development may be seen from many different points of view: in terms of history, theory or empirical generalization. The Political Economy of Development draws these points of view together as it explores the practice of economic development itself and considers the issues that arise in attempting to devise development strategies for developing countries and to implement them. The term 'political economy' highlights the fact that economics cannot be conducted in isolation, and always has to be related to the political and social setting of the countries with which it is concerned. The Political Economy of Development foregrounds the political context of development in its study of applied economics."--Bloomsbury Publishing